Beban Lebih Elektro Motor Pompa Ejektor Pada Fresh Water Generator di Atas Kapal Motor Penumpang Mutiara Ferindo II - Andi Hendrawan; Aris Sasongko D; Hasan Nasution (Jurnal Maritim Polimarin, 2022)
The ejector pump has two main components, namely the electro-motor part and the mechanical part. The electro motor plays a vital role in the activity of draining sea water to the fresh water generator. The electro motor acts as a rotary driver in pump mechanics which has the working principle of converting electrical energy into mechanical energy. Control system and electro protection. The purpose of this research is to determine the cause of overload on a mechanical motor pump. The research was conducted by observation, namely direct observation of the pump which functions as an auxiliary machine. The results show that because the bearings experience excessive heat due to the connection at the center of the motor with the pump not being centered. Gland packing experiencing high speed events so that the shaft is difficult to rotate.